Analisis pengaruh kualitas layanan, corporate image, dan customer relationship management terhadap loyalitas nasabah dengan kepuasan nasabah sebagai variabel intervening - Kuswandarini, Krisna Issri; Annisa, Arna Asna (Journal of Management and Digital Business, 2021)
This study aims to determine and analyze the influence of service quality, corporate image, and customer relationship management (CRM) on customer loyalty with customer satisfaction as an intervening variable (study at Bank Syariah Indonesia branch office Semarang). This research is a quantitative research using primary data. The analysis method uses a path analysis approach. The test results show that service quality, customer relationship management, and satisfaction positively affect loyalty. The corporate image does not affect loyalty. Service quality and corporate image have no positive effect on satisfaction. Customer relationship management has a positive effect on satisfaction. Path analysis test shows that the satisfaction variable acts as a mediation between the influence of service quality, corporate image, customer relationship management on customer loyalty at bank BSI branch office Semarang.